Problems and prospects development of the tourism industry in Ukraine - Kosenko, S. A.; Pererva, P. G. (My University, 2023)
It has been proven that Ukraine has a huge potential, which is confirmed by its natural, historical, cultural and human factors. But one of the main problems of the Ukrainian tourism industry is insufficient funding from both the government and foreign investors.
Проблеми та перспективи розвитку індустрії туризму в Україні
Keywords: tourism business; development; market; demand; supply; enterprises